Arabic writing in the digital age towards a theoretical framework - Khalil, Saussan (London New York Routledge, Taylor & Francis Group, 2022)
"The written and spoken forms of Arabic have been traditionally viewed as separate forms of the language that rarely overlap in writing, but this book will examine the recently emerged concept of 'mixed' writing that combines both written and spoken forms. This book takes a close look at different examples of mixed Arabic writing in modern (20-21st century) print and online literature, offering an analysis of this type of mixing alongside a dynamic model for analysing mixed Arabic writing, and the motivations for producing this type of writing. This book further introduces the ground-breaking concept of the seven writing styles for Arabic, ranging from Classical Arabic to ChatSpeak, whilst also offering an overview of early Arabic literacy and children's literature. Primarily aimed at Arabic researchers and teachers in linguistics, sociolinguistics, identity studies, politics and Teaching Arabic as a Foreign Language, this book would also be informative for undergraduate and postgraduate students studying Arabic as foreign language, Arabic linguistics, and dialectology"--
Includes bibliographical references and index
Keywords: Written communication -- Egypt; Arabic language -- Egypt -- Written Arabic; Arabic language -- Egypt -- Spoken Arabic; Arabic language -- Egypt -- Social aspects